Teachers Training and Multicultural Education: the role of the Programa Residência Pedagógica Biologia (PRPBio) (Research, Society and Development, 2022)
The purpose of this article is to evaluate the role of the Programa Residência Pedagógica Biologia (PRPBio) in the preparation of teachers and university students, in dialogue with a multicultural education perspective, who are both active in the educational setting. As a result, the choice was made to use a qualitative methodology that made use of the technique of participatory observation while doing the fieldwork using daily logs that were analyzed with support from Freire's concepts. The activities described and analyzed were developed in a public school, in Fortaleza, with participation from PRPBio students in the field of natural sciences. According to the research parameters, the individuals involved in the narratives are not identified. The findings point to the development of a reflective mindset, with a multicultural orientation, about the reality of action, acting directly toward social transformation after developing provocative activities with pertinent social issues. Conclusion: The PRPBio provides an opportunity for university and school collaboration and dialogue to develop innovative educational practices that support teacher preparation and independent student development.